E-Comic Based on Problem Solving for Fraction Material in Grade IV Elementary Mathematics - Gusti Ayu Dian Putri Rahayu; I Wayan Wiarta; I Gusti Agung Ayu Wulandari (Mimbar Ilmu, 2025)
The lack of student engagement and the limited use of contextual media in elementary school mathematics learning have driven the need for the development of innovative problem-solving-based e-comics to enhance understanding and learning motivation. The purpose of this study is to develop a problem-solving-based e-comic learning medium that is valid, practical, and effective in improving mathematics learning outcomes. This research is a type of research and development (R&D) using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The research subjects included design experts, content experts, instructional design experts, media experts, and 14 fourth-grade elementary school students. Data were collected qualitatively and quantitatively through interviews, questionnaires, and tests to assess teacher needs, student responses, and effectiveness. The results of the media feasibility assessment from subject matter experts (92%), instructional design experts (92.5%), learning media experts (91%), individual trials (92.5%), and small group trials (93.6%) all fell into the "very good" qualification. The one-sample t-test results showed that tcount (3.022) > ttable (1.770) at a 5% significance level. In conclusion, the problem-solving-based e-comic learning medium is effective in improving mathematics learning outcomes of fourth-grade elementary school students. The implication is that this medium can be used as an alternative learning tool that is more engaging and effective.